2004
DOI: 10.1021/jp049323y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Oxidation of Porous Silicon:  Study on Reaction Kinetics

Abstract: Porous silicon (PS) samples obtained by dark etching of p + -type silicon wafers are oxidized in dry air, at various temperatures from 200 °C up to 800 °C for 1-20 h durations, to determine the kinetics of the reaction. The extent of oxidation calculated from mass gains is plotted as a function of oxidation time and temperature. By fitting the general reaction kinetic solutions of different-order reactions, one finds that the function valid for first-order kinetics gives the best matches. From the obtained rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…4. Similar results are also observed by several authors [22,23]. The high reactivity of PSi for oxidation may arise from peculiar internal strain induced in nanostructured substances [26,27].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…4. Similar results are also observed by several authors [22,23]. The high reactivity of PSi for oxidation may arise from peculiar internal strain induced in nanostructured substances [26,27].…”
Section: Resultssupporting
confidence: 89%
“…(1) for PSi (solid squares) and bulk Si samples (solid circles) as a function of the annealing temperature T. We can see the clear difference of the SiO 2 thickness between for the PSi and bulk Si samples. In the literature [22,23], it is reported that the oxidation of PSi gives two different activation energies. In our case, since the SiO 2 thickness on the PSi surface increases with two steps (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…110,[476][477][478] Many oxidation methods exist, such as aging in ambient, 479 exposure to water vapor, [480][481][482] anodic oxidation in a non-fluoride electrolyte, 142,179,[483][484][485] 479 and thermal oxidation in wet and dry O 2 fluxes, 189,381,[488][489][490][491] including rapid thermal oxidation. 477 A data review regarding a wide range of oxidation treatments (e.g., thermal treatments, electrochemical and chemical oxidation, pthotochemical oxidation, etc.)…”
Section: Oxidation Of Porous Simentioning
confidence: 99%
“…110 Since porous Si has a very large surface-to-volume ratio, it is being oxidized already at 750 to 800 • C (see Figure 87). For example, Pap et al 490 have shown that already at T = 800 • C after 10 h oxidation the whole PSi structure with wall thickness ∼30 nm was oxidized.…”
Section: Oxidation Of Porous Simentioning
confidence: 99%
“…Several (110) PSi membranes of various thicknesses were fabricated and transferred to a glass substrate in which a 3-to 4-mm circular hole was made in order to characterize the birefringence as a function of optical path. Before measuring the birefringence of the fabricated samples, a thermal oxidation at 200°C for 12 h was carried out in order to stabilize pore surfaces during the measurements [46]. The optical anisotropy of fabricated samples was then determined by analyzing the state of polarization of the light transmitted through them [47].…”
Section: Positive Measurements and Discussionmentioning
confidence: 99%